Reptile Diversity on Several Habitat Types Utilization Blocks of Integrated Educational Conservation Forest, Wan Abdul Rachman Great Forest Park - Ihza Wijaya; Bainah Sari Dewi; Yulia Rahma Fitriana; Arief Darmawan (University of Lampung, 2022)
Reptiles are part of biodiversity which has an important role in maintaining the balance of the ecosystem, information on the diversity of reptiles in the Wan Abdul Rachman Forest Park (Tahura WAR) is very important to support reptile conservation efforts. This study aims to compare the diversity of reptiles in several different habitat types, 1) rivers, 2) secondary forests, 3) Shrubs. The method used in amphibian data collection is the Visual Encounter Survey (VES) with the transect method, the length of the transect line used is 300-400 meters with 6 repetitions for each habitat type. Data analysis by calculating the Shannon-Wiener species diversity index and evenness index. Identify the reptile using the manual. The results of observations found as many as 57 individuals consisting of 7 species and 5 families: Agamidae 2 species, Scincidae 1 species, , Lacertidae 1 species, Elapidae 1 species and Colubridae 2 species. There are 4 species of river, 6 species of secondary forest habitat, and 2 species of river habitat. The value of amphibian diversity in the river habitat type and secondary forest was categorized as moderate, and the bush habitat type was categorized as low, and the evenness value in three habitats, namely, river E=0.83, secondary forest E=0.76 and bush habitat E=0.96 with stable category.